Working retirees in Taiwan: examining determinants of different working status after retirement - Tai-Kang Wu; Li-Jung Elizabeth Ku; Jer-Hao Chang; Ching-Ju Chiu; Susan C. Hu (BMC Geriatrics, 2024)
Abstract This study aims to investigate the factors influencing the work status of retirees after retirement, especially focusing on self-employment and unpaid work. Data was taken and analyzed from the “Taiwan Health and Retirement Study,” a nationally representative sample of retired personnel aged 50–74 in 2015–2016. Four types of work status were classified after retirement: Fully retired, Paid work, Self-employment, and Unpaid work. Multinomial regression analysis was used to explore the factors related to participation in paid, self-employed, and unpaid work. Results show that pre-retirement occupation was significantly associated with paid work after retirement. For example, retirees in Taiwan who were employed by private enterprises or self-employed before retirement were more likely to engage in paid work after retirement than civil servants before retirement. Two other factors, namely pre-retirement job stress and work flexibility, prolong the careers of retired workers, especially in self-employment and unpaid work after retirement. Gender also significantly affects the choice of work after retirement. These findings can be used as a reference for future policies on the aging labor force.